2018
DOI: 10.17219/acem/76160
|View full text |Cite
|
Sign up to set email alerts
|

An initial evaluation of cytotoxicity, genotoxicity and antibacterial effectiveness of a disinfection liquid containing silver nanoparticles alone and combined with a glass-ionomer cement and dentin bonding systems

Abstract: Porenczuk A, Grzeczkowicz A, Maciejewska I, et al. An initial evaluation of cytotoxicity, genotoxicity and antibacterial effectiveness of a disinfection liquid containing silver nanoparticles alone and combined with a glass-ionomer cement and dentin bonding systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28]. Contradictory, other studies found that Etch-and-Rinse adhesives were more cytotoxic [11,17,[20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28]. Contradictory, other studies found that Etch-and-Rinse adhesives were more cytotoxic [11,17,[20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to the quantitative assessment, every adhesive showed a statistically significant difference to the cell control regarding the qualitative evaluation including the reactivity index. Thus, all the adhesives showed a cytotoxic effect, which is in accordance with previous studies [11,[15][16][17][18]21,27,29,32]. The ranking of the cytotoxicity of monomers [43,46,47] cannot be confirmed with significant differences by the qualitative results and the reactivity index.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations